“Princess and the pea”: an assessment tool for palpation skills in postgraduate education - Kamp, Rainer; Möltner, Andreas; Harendza, Sigrid (BMC medical education, 2019)
In osteopathic medicine, palpation is considered to be the key skill to be acquired during training. Whether palpation skills are adequately acquired during undergraduate or postgraduate training is difficult to assess. The aim of our study was to test a palpation assessment tool developed for undergraduate medical education in a postgraduate medical education (PME) setting.
Gesehen am 02.07.2019